Jahrbuch der Akademie der Wissenschaften zu Göttingen. 2019 - Akademie der Wissenschaften zu Göttingen (Universitätsverlag Göttingen, 2021)
With its Yearbook, the Göttingen Academy of Sciences and Humanities gives an account of its activities in 2019. The yearbook contains the activity report of the president and the work reports of the research projects, in addition to academy lectures and lectures by award winners. The new members introduce themselves and the deceased are honored.